The Influence of Knee Osteoarthritis on Spinopelvic Alignment and Global Sagittal Balance - Katsumi, Ryota; Mannen, Erin M.; Bajaj, Gitanjali; Smith, Jacob R.; Mears, Simon C.; Stambough, Jeffrey B.; Barnes, C. Lowry (The Journal of Knee Surgery, 2022)
Osteoarthritis (OA) of the knee is thought to lead to a loss of lumbar lordosis (LL) as a compensation for knee flexion contracture. Changes in sagittal alignment are not limited to the lumbar spine and involve a complex interplay of alignment of the hip, pelvis, and spine. While spine–hip interactions have been previously explored, the influence of knee OA sagittal alignment parameters on spinopelvic alignment and global sagittal balance remains unexplored. Standing radiological examination using EOS biplanar radiography was examined in 108 patients with knee OA. Whole-body sagittal alignment parameters (thoracic kyphosis, LL, pelvic incidence, pelvic tilt [PT], femoropelvic angle [FPA], femoral tilt angle [FTA], tibial tilt angle, and knee flexion angle [KFA]) and global balance parameters (sagittal vertical axis [SVA] and odontoid hip axis [OD-HA] angle) were measured three dimensionally (3D). The correlation coefficients among all parameters were assessed. A multiple stepwise linear regression model was built to investigate the direct association between SVA or OD-HA angle (dependent variables) and sagittal alignment parameters and demographic data (independent variables). Significant correlations between KFA, FPA, FTA, SVA, and OD-HA angle were found. FTA was correlated with LL and FPA. The FTA was the most influential predictor of both global sagittal balance parameters (p < 0.001). Knee OA leads to changes in global sagittal balance with effects at the hip, knee, pelvis, and spine. FTA (forward flexion of the femur vs. the vertical plane) is the largest driver of global sagittal plane balance in patients with knee OA.
Keywords: knee–spine syndrome; lumbar lordosis; knee flexion contracture; knee osteoarthritis; spinal deformity; sagittal alignment